Ответы и объяснения

Лучший Ответ!
2014-01-15T16:39:30+00:00
№1
1)3х - 2 = 5.
   3х = 5 + 2.
   3х = 7
   х =  \frac{7}{3} = 2 \frac{1}{3}
2) 5х - 2х + 3 = 6.
    3х = 6 - 3.
    3х = 3.
    х = 1.
3) 8 -  \frac{3}{5} x = 14.

 \frac{3}{5} x = -6
x = -6 : 0,6 = - 10.

№2
Пусть х - задуманное число.
5х - 12 = 38.
5х = 50.
х = 10.
№3
пусть Х м - в одном.
         (х + 7) - в другом.
Всего 23 м.
1) х + (х + 7) = 23.
2х = 16.
х = 8.

8 м - в одном. 
2) 8 + 7 = 15 (м) - в другом.
№4
Не видно.
№5
2х - 3 - (5х - 4) = 2х - 3 - 5х + 4 = 1 - 3х.
№6
3(2х - 1) - 2(5х - 4) - (2 - 4х) = 6х - 3 х - 10х + 8 - 2 + 4х =6 - 3х.
Да, значение выражения зависит от значения Х.